Diabetes mellitus and risk of ischemic stroke in patients with heart failure and no atrial fibrillation. (15th April 2016) - Melgaard, Line; Gorst-Rasmussen, Anders; Søgaard, Peter; Rasmussen, Lars Hvilsted; Lip, Gregory Y.H.; Larsen, Torben Bjerregaard
Abstract: Objective: The risk of ischemic stroke, systemic thromboembolism, and all-cause death among heart failure patients previously diagnosed with diabetes mellitus is poorly described. We evaluated the risk of these endpoints among heart failure patients without diagnosed atrial fibrillation according to the presence of diabetes mellitus. Methods: Population-based nationwide cohort study of non-anticoagulated patients diagnosed with incident heart failure during 2000–2012, identified by record linkage between nationwide registries in Denmark. We calculated relative risks after 1 year to evaluate the association between diabetes and risk of events in 39, 357 heart failure patients, among whom 18.1% had diabetes. Analysis took into account competing risks of death. Results: Absolute risks of all endpoints were higher in patients with diabetes compared to patients without diabetes after 1-year follow-up (ischemic stroke: 4.1% vs. 2.8%; systemic thromboembolism: 11.9% vs. 8.6%; all-cause death: 22.1% vs. 21.4%). Diabetes was significantly associated with an increased risk of ischemic stroke (adjusted relative risk [RR]: 1.27, 95% confidence interval [CI]: 1.07–1.51); systemic thromboembolism (RR: 1.20, 95% CI: 1.11–1.30); and all-cause death (RR: 1.17, 95% CI: 1.11–1.23). Additionally, time since diabetes diagnosis was associated with higher adjusted cumulative incidences of ischemic stroke, systemic thromboembolism, and all-cause death ( p for trend, p  < 0.001). Conclusions: Among heart failure patients without atrial fibrillation, diabetes was associated with a significantly increased risk of ischemic stroke, systemic thromboembolism, and all-cause death compared to those without diabetes, even after adjustment for concomitant cardiovascular risk factors. Increased focus on secondary prevention in heart failure patients with diabetes may be warranted.